Economy and creativity multiparametric clustering - Svitlana Slava (REGION, 2023)
This paper suggests a way to cluster Ukrainian regions by using economy and creativity-related multiparametric sets so as to reveal the main roles of players in cross-regional comparisons. Special attention was paid to an analysis of invaded regions since 2014 and 2022. The methodology is based on a consistent utilisation of structured analysis, correlation, regression and clustering modelling. Sets of parameters were selected from secondary data via correlation and regression analyses aimed at defining the most impactful factors. The study sample includes 25 regions in Ukraine. The research results contribute mainly to the theorisation of comparative regional analysis and to the relationship between the economy and creativity and their specific behaviour in regions directly linked to war crisis.